The knowledge, attitudes and perceptions of physiotherapists in KwaZulu-Natal, South Africa, towards mental health - Marilyn Hooblaul (South African Journal of Physiotherapy, 2020)
Background: Physiotherapists are trained to manage patients with physical needs, but because of limited training at an undergraduate level in mental health, patients may not receive holistic care. This lack of knowledge often can deny people living with a mental illness (PLWMI) the potential benefits of physiotherapy treatment and exercise.